On a Convergence of Formal Power Series Under a Special Condition on the Gelfond-Leont'ev Derivatives - Sheremeta, M. M.; Volokh, O. A. (Журнал математичної фізики, аналізу, геометрії, 2007)
For a formal power series the conditions on the Gelfond-Leont'ev derivatives are found, under which the series represents a function, analytic in the disk {z : |z| < R}, 0 < R ≤ +∞. Mathematics Subject Classification: 30D50, 30D99.